2022
DOI: 10.1029/2021je007102
|View full text |Cite
|
Sign up to set email alerts
|

Martian Dust Storms and Gravity Waves: Disentangling Water Transport to the Upper Atmosphere

Abstract: Simulations with the Max Planck Institute Martian general circulation model for Martian years 28 and 34 reveal details of the water “pump” mechanism and the role of gravity wave (GW) forcing. Water is advected to the upper atmosphere mainly by upward branches of the meridional circulation: in low latitudes during equinoxes and over the south pole during solstices. Molecular diffusion plays little role in water transport in the middle atmosphere and across the mesopause. GWs modulate the circulation and tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
(87 reference statements)
2
15
0
Order By: Relevance
“…It may be noted that GW amplitudes are damped in the lower atmosphere during dust storms (Heavens et al 2020;Kuroda et al 2020). The enhanced GWs in the thermosphere have implications for the transport of water to the upper atmosphere and to escape of hydrogen to the outer space (Yiğit et al 2021a;Shaposhnikov et al 2022). Yiğit et al (2021a) have shown that a 40% increase in GW amplitudes doubles the hydrogen escape flux through the thermal escape mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be noted that GW amplitudes are damped in the lower atmosphere during dust storms (Heavens et al 2020;Kuroda et al 2020). The enhanced GWs in the thermosphere have implications for the transport of water to the upper atmosphere and to escape of hydrogen to the outer space (Yiğit et al 2021a;Shaposhnikov et al 2022). Yiğit et al (2021a) have shown that a 40% increase in GW amplitudes doubles the hydrogen escape flux through the thermal escape mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Yiğit et al (2021a) have shown that a 40% increase in GW amplitudes doubles the hydrogen escape flux through the thermal escape mechanism. Shaposhnikov et al (2022) have shown that the GWs alter the timing and intensity of the water transport to the upper atmosphere. Therefore, the analysis of the present study that disentangles the complex variabilities in the GW amplitudes and isolates the contributions of different drivers will be helpful to assess the role of GWs on the water transport and on the hydrogen escape under different solar, dust, and seasonal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated in the three‐dimensional Mars GCM simulations of Medvedev, Yiğit, Hartogh, and Becker (2011), which interactively included a non‐orographic, whole atmosphere, spectral gravity wave parameterization (Yiğit et al., 2008). In addition to the strong dynamical forcing from GW momentum deposition, further Mars GCM studies have shown that GWs significantly cool the lower thermosphere (Medvedev & Yiğit, 2012), facilitate CO 2 ice cloud formation (Yiğit et al., 2018), and modulate the circulation and temperature during global dust storms, thus changing the timing and intensity of the water transport into the upper atmosphere (Shaposhnikov et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…All modes are characterized by sharp rises of water vapor, yet they differ in the way the atmosphere controls these rises. For instance, the MY34 GDS occurred at a time when the equinoctial circulation dominates, with a dual cell pattern centered about the equator where the rising region is thus located (Neary et al., 2020; Shaposhnikov et al., 2022). In contrast, the rise occurring around perihelion coincides with the southern solstice circulation pattern, with a single cell whose rising branch is positioned in the mid‐to‐high southern latitudes.…”
Section: Resultsmentioning
confidence: 99%